Impact of cigarette smoking on mortality in HIV-positive and HIV-negative veterans. - Crothers, Kristina; Goulet, Joseph L; Rodriguez-Barradas, Maria C; Gibert, Cynthia L; Oursler, Krisann K; Goetz, Matthew Bidwell; Crystal, Stephen; Leaf, David A; Butt, Adeel A; Braithwaite, R Scott; Peck, Robin; Justice, Amy C (AIDS education and prevention : official publication of the International Society for AIDS Education, 2009)
It is unknown whether smoking confers similar mortality risk in HIV-positive as in HIV-negative patients. We compared overall mortality stratified by HIV and smoking of 1,034 HIV-positive block-matched to 739 HIV-negative veterans, enrolled 2001-2002 in the Veterans Aging Cohort 5 Site Study. Adjusted incidence rate ratios (IRR) for mortality were calculated using Poisson regression. Mortality was significantly increased in HIV-positive veterans according to both smoking status and pack-years in unadjusted and adjusted analyses (adjusted IRR 2.31, 95% confidence interval [CI] 1.53-3.49 for HIV-positive current smokers and IRR 1.32, 95% CI 0.67-2.61 for HIV-negative current smokers). Comorbid diseases were also significantly increased according to smoking status and pack-years. Current smoking is associated with poor outcomes; even lower levels of exposure appear to be detrimental in HIV-infected veterans. These findings support the need for improvements in smoking cessation and for studies of mechanisms and diseases underlying increased mortality in smokers with HIV.
Keywords: Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Cohort Studies; Comorbidity; Female; HIV Infections; HIV Seronegativity; HIV Seropositivity; HIV-1; Humans; Male; Middle Aged; Proportional Hazards Models; Quality of Life; Smoking; Survival Analysis; United States; Veterans; Viral Load